Living I Was Your Plague : Martin Luther's World and Legacy - Roper, Lyndal (Book collections on Project MUSE., 2021)
"Martin Luther inspired strong emotions not only in his religious and political opponents, but also in those who knew him. People either loved or hated him, and even today he can elicit intense emotional reactions. Always a controversial figure, his influence is nonetheless pervasive, particularly in Germany where he has left an indelible imprint on the culture, musical, linguistic, material, and visual. This book reflects on the way Martin Luther carefully crafted an image of himself, how others portrayed him for their own purposes (both during his life and after), and the ongoing legacy of these images. Though Luther had a magnetic quality both in life and in death, Roper does not shy away from discussing and grappling with his less savory side. Luther was highly aggressive and could be foul-mouthed, especially when speaking of his enemies. He was virulently anti-Semitic and he tended toward misogyny, even for a man of his time. Moving nimbly from analysis of Luther's portraits to his dreams, his anti-Pope propaganda, and even the Playmobil Luther figures of today, Roper presents new sides of this complicated man made more complicated by his followers and detractors"--